Birth weight at term at different altitudes in Peru - Villamonte, Wilfredo (2015)
Objectives: To determine birth weight at different levels of altitude and relation with sex of newborns. Design: Descriptive and retrospective study. Settings: Lima, Arequipa, Cusco, Puno and Cerro de Pasco EsSalud hospitals. Participants: Normal term neonates. Interventions: Birth weight of 19 543 normal neonates at term from normal singleton pregnancies recorded between 2001 to 2005 by the Peruvian Social Health Security Perinatal Information System database were analyzed in the cities of Lima (150 m), Arequipa (2 340 m), Cuzco (3 400 m), Puno (3 830 m) and Cerro de Pasco (4 340 m). Main outcome measures: Weight and sex of newborns. Results: There were significant differences in newborns at term birth weight in the five cities studied (p < 0.05). History of abortions, and current cesarean sections and sex of newborns were similar in all groups. Conclusions: Difference in mean birth weight at term was around 55 g in the first four cities, but increased between Puno and Cerro de Pasco in about 250 g. Significant reduction in birth weight occurred over 2 340 m and much more over 4 000 m. Male babies were heavier than female babies at different altitudes.